2018
DOI: 10.3390/ma11040490
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenic Potential of Pre-Osteoblastic Cells on a Chitosan-graft-Polycaprolactone Copolymer

Abstract: A chitosan-graft-polycaprolactone (CS-g-PCL) copolymer synthesized via a multi-step process was evaluated as a potential biomaterial for the adhesion and growth of MC3T3-E1 pre-osteoblastic cells. A strong adhesion of the MC3T3-E1 cells with a characteristic spindle-shaped morphology was observed from the first days of cell culture onto the copolymer surfaces. The viability and proliferation of the cells on the CS-g-PCL surfaces, after 3 and 7 days in culture, were significantly higher compared to the cells cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…However, only a few studies have examined the potential of CS-g-PLLA copolymers as biomaterials for tissue engineering [25,32]. Recent reports from our research group focused on the development of CS grafted with polycaprolactone chains, demonstrating their potential in hard and soft tissue engineering, as they support the proliferation of pre-osteoblastic cells [56], Wharton's jelly mesenchymal stem cells [35,52], and macrophages, acting as an immunoregulator for their polarization [57].…”
Section: Discussionmentioning
confidence: 99%
“…However, only a few studies have examined the potential of CS-g-PLLA copolymers as biomaterials for tissue engineering [25,32]. Recent reports from our research group focused on the development of CS grafted with polycaprolactone chains, demonstrating their potential in hard and soft tissue engineering, as they support the proliferation of pre-osteoblastic cells [56], Wharton's jelly mesenchymal stem cells [35,52], and macrophages, acting as an immunoregulator for their polarization [57].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to hydroxyapatite, other composites, such as nano-zirconia/CS, nano-calcium zirconate/CS, and strontium-modified CS/montmorillonite composites with comparable mechanical properties were designed [63,64]. It was shown that MC3T3-E1 pre-osteoblastic cells when cultured on a CS-graft-polycaprolactone copolymer surface, in comparison to a tissue culture-treated polystyrene surface, show significantly higher alkaline phosphatase activity, deposition of calcium, and ECM synthesis [65]. For example, the addition of hydroxyapatite or bioglass to the matrix led to a compressive strength increase compared to CS alone.…”
Section: Bonementioning
confidence: 99%
“…The only difference is a small change in peak shape at the 1170 cm −1 spectral band: a possible sign of glycosidic stretching happening at the very high end of the characteristic wavenumbers for this type of bond 30,63,65. However, since other expected changes after the addition of chitosan,66 such as the appearance of the fingerprint of the glycosidic bond in the 1000–1100 cm −1 range or the increase in intensity in correspondence of amine and amide bond vibrations (νN‐H, δN‐H, and ωN‐H at 3400, 1600, and 700 cm −1 , respectively30,67) did not occur, it is unlikely that the change in shape at 1170 cm −1 is due to chitosan. Most probably, the variation is clueing to the occurrence of minor acid catalyzed hydrolysis of polycaprolactone during the dissolution of the polymer in acetic and formic acid 68.…”
Section: Resultsmentioning
confidence: 98%